First-line glaucoma monotherapy medication patterns in Finland during 1995–2019 based on a population-based study - Petri K. M. Purola; Seppo V. P. Koskinen; Hannu M. T. Uusitalo (PLoS ONE, 2025)
Background The long-term patterns in first-line glaucoma medication are not well established. Exploring these in longitudinal and population-based settings would provide information for the healthcare systems to plan glaucoma care accordingly. Objective To evaluate patterns in first-line glaucoma monotherapy in Finland during 1995–2019 based on nationwide survey and register data. Methods A population-based cohort study with 25 years of total follow-up. The cohort (n = 9288) is a random sample drawn from the nationwide health examination survey FinHealth 2017 which represents the Finnish population aged 30 years or older in 2017. Glaucoma patients were selected from the survey participants based on linked register data that included prescriptions and special reimbursements for glaucoma medication. The patterns, length of use, age at initiation, and persistence of first-line glaucoma drug monotherapies were observed during 1995–2019. Results A total of 141 glaucoma patients with glaucoma drug monotherapy as a first-line glaucoma therapy were identified from the sample. The proportion of patients continuing with their first-line monotherapy was 64% after 1 year, 37% after 3 years, and 21% after 5 years of follow-up. During the 25 years there was a shift from beta-blockers to prostaglandin analogues as the prominent first-line glaucoma drug class. The length of use was longer for prostaglandin analogues compared with beta-blockers among patients continuing with their first-line monotherapy after 5 years of follow-up. The non-persistence rate was 38% of all patients during their first-line monotherapy. Timolol fixed-combinations were the most common second-line glaucoma therapy with a share of 39% after 5 years of follow-up. Conclusions During the 25-year follow-up a shift from beta-blockers to prostaglandin analogues had occurred and long initial therapies of over 5 years had become more common. However, the decline in the continuation of the initial therapy still occurred early with 1 out of 3 patients continuing after 3 years. This decline together with the consistent problem of non-persistence remain clinical challenges in topical drug therapy of glaucoma.